PERFORMANCE ANALYSIS OF STREET AHMAD YANI KM 27 DUE TO THE SP. ROAD REHABILITATION WORK PROJECT. LIANG ANGGANG - BTS. TRAINING CITY SECTION 1 BANJARBARU CITY - Khalikinor, M. Ikhsan; Yasruddin, Yasruddin (Universitas Lambung Mangkurat, 2024)
In this study, an analysis of the calculation of traffic volume, vehicle speed and side friction that occurred as a result of the Sp. Road Rehabilitation Project was carried out. Liang Anggang - Bts. Pelaihari City Section 1 Banjarbaru City using the 1997 Indonesian Road Capacity Manual (MKJI) method. Traffic volume conditions on Jalan Ahmad Yani Km 27 as a result of the Sp. Road Rehabilitation Project. Liang Anggang - Bts. Pelaihari City Section 1 City of Banjarbaru on Sunday, January 23, 2022 in the direction of Banjarbaru to Liang Anggang for 3007 vehicles/day, while the direction from Liang Anggang to Banjarbaru is 3041 vehicles/day.The traffic capacity for Jalan Ahmad Yani Km 27 which has a population of 258,753 people, with a city size of 0.1 - 0.5. Analysis data for Jalan Ahmad Yani Km 27 as a result of the Sp. Road Rehabilitation Project. Liang Anggang - Bts. Pelaihari City Section 1, Banjarbaru City on Sunday, January 23, 2022 in the direction of Banjarbaru towards Liang Anggang 3007. With MC 73.46%, LV 15.76%, HV 10.31%, and UM 0.47%. while the direction of Liang Anggang is towards Banjarbaru 3041. With MC 73.04 %, LV 15.36%, HV 11.15%, and UM 0.46%.The average speed that occurs on Jalan Ahmad Yani Km 27 due to the Road Rehabilitation Project Sp. Liang Anggang - Bts. Pelaihari City Section 1, Banjarbaru City on Sunday, January 23, 2022, headed from Banjarbaru to Liang Anggang with an average speed of MC 25.45 km/hour, LV 24.12 km/hour, HV 23.47 km/hour. while the direction of Liang Anggang is towards Banjarbaru with an average speed of MC 25.38 km/hour, LV 24.16 km/hour, HV 23.47 km/hour.The traffic density that occurred on Jalan Ahmad Yani Km 27 as a result of the Sp. Road Rehabilitation Project. Liang Anggang - Bts. Pelaihari City Section 1, Banjarbaru City on Sunday, January 23, 2022 in the direction of Banjarbaru towards Liang Anggang with a traffic density of 86.81 vehicles/hour, LV 19.65 vehicles/hour, HV 13.21 vehicles/hour. while the Liang Anggang direction is towards Banjarbaru with a traffic density of MC 87.52 vehicles/hour, LV 19.33 vehicles/hour, HV 14.44 vehicles/hour. Keywords: Capacity, Speed and Density and MKJI 1997